Cerebrospinal fluid devices infection. How are we? (Actualizaciones en Sida e Infectología, 2024)
Infection is the most common complication of cerebrospinal fluid (CSF) devices. The organisms adhere to the surface and form a biofilm, which difficults clinical diagnosis, laboratory and treatment. OBJECTIVES: Incidence of infection, isolated microorganisms, risk factors, reinfection rate and mortality in a neurosurgical reference hospital. MATERIAL AND METHODS: Retrospective, analytical, observational cohort study. Inclusion criteria: over 15 years old, with CSF devices: EVD and IVD. Period: From June 1, 2020 to June 1, 2022. p
Keywords: external ventricular device - internal ventricular device - ventriculo peritoneal shunt infection, ventriculitis, risk factors.